M-learning as a tool for adaptive learning: A proposal for higher education - Ramírez Hernández, Moramay; León Pérez, Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In recent years, university education has been rapidly transformed, student performance, technological advances and the pandemic have generated new challenges. The adaptive learning is an alternative that can be implemented to identify academic strengths and weaknesses and together with the Information Technology applied to education is possible to improve the academic performance of students by making them protagonists of their learning. This work aim to design an adaptive learning component model to facilitate the development of skills in the area of programming methodology.